2019
DOI: 10.1167/tvst.8.2.16
|View full text |Cite
|
Sign up to set email alerts
|

A Workshop on Measuring the Progression of Atrophy Secondary to Stargardt Disease in the ProgStar Studies: Findings and Lessons Learned

Abstract: The Progression of Atrophy Secondary to Stargardt Disease (ProgStar) studies were designed to measure the progression of Stargardt disease through the use of fundus autofluorescence imaging, optical coherence tomography, and microperimetry. The overarching objectives of the studies were to document the natural course of Stargardt disease and identify the most appropriate clinical outcome measures for clinical trials assessing the efficacy and safety of upcoming treatments for Stargardt disease. A wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…Indeed, two different types of decreased autofluorescence have been proposed based on the measurement of relative of darkness with respect to the optic nerve head (or, if not present in the image, the retinal vessels), considered as the reference for 100% blackness on the gray scale: definitely decreased autofluorescence (DDAF), defined as a signal more than 90% black in reference to the optic nerve head, and questionably decreased autofluorescence (QDAF), defined as 50% to 90% black, as compared to the reference 53. Areas of QDAF tend to be unstable on consecutive examinations; they have been interpreted as a transition state between healthy retina and regions of advanced disease (ie, DDAF).…”
Section: Monitoring Progression Of Stgd1mentioning
confidence: 99%
“…Indeed, two different types of decreased autofluorescence have been proposed based on the measurement of relative of darkness with respect to the optic nerve head (or, if not present in the image, the retinal vessels), considered as the reference for 100% blackness on the gray scale: definitely decreased autofluorescence (DDAF), defined as a signal more than 90% black in reference to the optic nerve head, and questionably decreased autofluorescence (QDAF), defined as 50% to 90% black, as compared to the reference 53. Areas of QDAF tend to be unstable on consecutive examinations; they have been interpreted as a transition state between healthy retina and regions of advanced disease (ie, DDAF).…”
Section: Monitoring Progression Of Stgd1mentioning
confidence: 99%
“…The clinical course of STGD1 is heterogeneous, and little is known about factors predicting the natural history of the disease. 3 , 4 The anticipation of patients with a faster rate of RPE-atrophy enlargement may be important in both clinical practice and research. The choice of the strategies and endpoints in therapeutic interventional trials may be different according to the predictive characteristics of each patient.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Progression of Atrophy Secondary to Stargardt Disease (ProgStar) Study group previously demonstrated good reproducibility of total retinal, EZ, and ONL thickness measurements on SD-OCT in a small subset (30 patients) of patients as part of a prospective natural history study 31 . However, numerous challenges to segmentation were encountered, including difficulty identifying boundaries for pathologic areas of layer disruption and algorithm failures that required tedious (6-8 h per eye) manual segmentation 32 . Our results demonstrate that OCT-based analysis of individual retinal sublayer thicknesses is feasible for the majority of Stargardt patients seen in an inherited retinal disease clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of photoreceptor and RPE loss in STGD1 are method-dependent, and most of the previously-published work has used en face imaging using short-wavelength autofluorescence (SW-AF) or near-infrared autofluorescence (NIR-AF). These methods analyze disease progression by tracking area of involvement but require atrophic loss of RPE cells to measure a discrete, hypo-autofluorescent border, which can sometimes be difficult to distinguish (e.g., determination of disease borders on SW-AF can be challenging due to accumulation of hyper-autofluorescent material in photoreceptor cells) 32 . Studies using en face SW-AF or NIR-AF imaging have suggested that the rate of RPE loss correlates with EZ loss, particularly when the total area of abnormal autofluorescence (hypo- and hyper-autofluorescence) are considered using SW-AF; however, using NIR-AF, RPE atrophy appears to precede detectable photoreceptor loss 11 , 14 , 45 47 .…”
Section: Discussionmentioning
confidence: 99%